2020
DOI: 10.3389/fphar.2020.00328
|View full text |Cite
|
Sign up to set email alerts
|

Bulleyaconitine A Exerts Antianxiety and Antivisceral Hypersensitivity Effects

Abstract: Visceral pain is one of the leading causes for abdominal pain in gastroenterological diseases and is still hard to treat effectively. Bulleyaconitine A (BAA) is an aconitine analog and has been used for the treatment of pain. Our previous work suggested that BAA exerted analgesic effects on neuropathic pain through stimulating the expression of dynorphin A in spinal microglia. Here, we investigated the inhibitory effect of BAA on visceral pain and examined whether the expression of dynorphin A in spinal microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…The results are in agreement with the previous publications that the κ-opioid receptor agonist salvinorin A punished self-administration of cocaine and remifentanil in monkeys (Freeman et al, 2014), and that addition of the κ-opioid receptor agonist U69,593 to fentanyl produced a proportion-dependent decrease of fentanyl self-administration in rats (Negus et al, 2008). In agreement, GNTI and other specific κ-opioid receptor antagonist nor-BNI (but not the μ-or δ-opioid receptor antagonist) blocked the antinociceptive effects of BAA (Li et al, 2016b;Huang et al, 2020b), bullatine A (Huang et al, 2016) and lappaconitine (Sun et al, 2018) in the rodent models of neuropathic pain, bone cancer pain, inflammatory pain and visceral pain.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results are in agreement with the previous publications that the κ-opioid receptor agonist salvinorin A punished self-administration of cocaine and remifentanil in monkeys (Freeman et al, 2014), and that addition of the κ-opioid receptor agonist U69,593 to fentanyl produced a proportion-dependent decrease of fentanyl self-administration in rats (Negus et al, 2008). In agreement, GNTI and other specific κ-opioid receptor antagonist nor-BNI (but not the μ-or δ-opioid receptor antagonist) blocked the antinociceptive effects of BAA (Li et al, 2016b;Huang et al, 2020b), bullatine A (Huang et al, 2016) and lappaconitine (Sun et al, 2018) in the rodent models of neuropathic pain, bone cancer pain, inflammatory pain and visceral pain.…”
Section: Discussionsupporting
confidence: 83%
“…As it is a nonnarcotic analgesic and has lower toxicity and wider treatment window than aconitine, BAA has been widely prescribed in China to treat various forms of chronic pain over four decades (Bello-Ramirez and Nava-Ocampo, 2004;Xie et al, 2018). Accumulated evidence demonstrated that BAA and its analogs aconitine (C19-diterpenoid), bullatine A (C20-diterpenoid) and lappaconitine (C18-diterpenoid) produced antinociception without induction of antinociceptive tolerance in various rodent models of pain hypersensitivity, including neuropathic pain, bone cancer pain, inflammatory pain, diabetic pain, and visceral pain (Li et al, 2016a;Li et al, 2016b;Huang et al, 2017a;Huang et al, 2020a;Huang et al, 2020b). Our recent studies further uncovered that BAA, aconitines, bullatine A and lappaconitine alleviated pain directly through stimulating spinal microglial dynorphin A expression and subsequent activating κ-opioid receptors in a variety of rodent models of pain hypersensitivity (Huang et al, 2017a;Li et al, 2017;Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results support that the antinociceptive effects of lappaconitine are entirely blocked by intrathecal injection of the specific dynorphin A antibody and κ-opioid receptor antagonist [29]. Interestingly, it seems that the alkaloids bioactive components from the medicinal plants of Ranunculus can induce the production of dynorphin A in the spinal cord [25,135,139]. Huang et al explored the analgesic mechanism of BA by studying the release of inflammatory factors and microglia dynorphin A.…”
Section: Regulation Of Alkaloids On Endogenous Opioid Peptides In Snlmentioning
confidence: 70%
“…Rats were given 30 minutes to accommodate the environment after they woke up. The balloon was then distended at four different pressures (20,40,60, and 80 mmHg) of graded colorectal distension. The distention at each pressure was maintained for 20 seconds at an interval of 5 minutes and repeated for three times.…”
Section: Evaluation Of Visceromotor Response To Graded Colorectalmentioning
confidence: 99%
“…In addition, it was proposed that activation of the descending inhibitory transmission by norepinephrine and serotonin was associated with the antinociceptive effects of BAA and its analogs mesaconitine, 3-acetylaconitine, and lappaconitine [9,16,17]. In contrast, our laboratory recently demonstrated that BAA and its analogs aconitine, bullatine, and lappaconitine, given subcutaneously or intrathecally, blocked the spinal nerve ligation-induced neuropathic pain by the stimulation of the spinal microglial expression of dynorphin A [10,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%